2022
DOI: 10.1108/ara-05-2021-0091
|View full text |Cite
|
Sign up to set email alerts
|

Betting against real earnings management

Abstract: PurposeThe study presents the zero investment strategies based on the pricing impact of real earnings management (REM) on stock returns after taking into account the direction and endogeneity nature of REM.Design/methodology/approachThe authors use standard portfolio methodology and Fama–Macbeth cross-sectional regression to analyze the data for this study. Both upward and downward form of REM has been examined. Accrual earnings management (AEM) has been controlled while examining the association between REM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Based on seminal studies, the overarching principle of REM is that to achieve short-term financial targets, firms manipulate earnings in the current period, but this is not sustainable (Graham et al ., 2005; Gunny, 2010; Roychowdhury, 2006; Zang, 2011). Countless studies infer that REM is a form of managerial opportunism based on the aforementioned inference (Agustia et al ., 2022; Bansal and Ali, 2022; Barghathi et al ., 2017; Bhatia et al ., 2019; Chapman and Steenburgh, 2011; Chen et al ., 2015; Choi et al ., 2021; Kiattikulwattana, 2014; Kim et al ., 2019; Luo, 2019; Mindzak and Zeng, 2018; Pappas et al ., 2019).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Based on seminal studies, the overarching principle of REM is that to achieve short-term financial targets, firms manipulate earnings in the current period, but this is not sustainable (Graham et al ., 2005; Gunny, 2010; Roychowdhury, 2006; Zang, 2011). Countless studies infer that REM is a form of managerial opportunism based on the aforementioned inference (Agustia et al ., 2022; Bansal and Ali, 2022; Barghathi et al ., 2017; Bhatia et al ., 2019; Chapman and Steenburgh, 2011; Chen et al ., 2015; Choi et al ., 2021; Kiattikulwattana, 2014; Kim et al ., 2019; Luo, 2019; Mindzak and Zeng, 2018; Pappas et al ., 2019).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Many prior studies in Indian institutional settings and other developing nations have suggested that different types of firm characteristics are useful in predicting earnings management (for instance, Adhikari et al ., 2021; Ali and Bansal, 2021; Bashir et al ., 2021; Bansal and Kumar, 2021; Bansal et al ., 2022, Bansal and Ali, 2022; Bansal and Bashir, 2023; Thomas et al ., 2022), hence we include a few variables such as firm size ( Size ), leverage ( Lev ), return on assets ( ROA), operating cash flows ( OCF ) and market to book value ( MTB ). We also include industry-fixed effects in model (2) to control for unobserved heterogeneity within industries.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, to ensure that our results are the outcome of shifting practices, we control for REM and AEM. We use an unexpected level of accruals (A_ACC) to measure AEM, an unexpected level of discretionary expenditure (A_DISX), and an unexpected level of production costs (A_PROD) to measure REM, consistent with many prior studies (for instance, Bansal and Ali, 2022;Bansal and Kumar, 2021). We control for certain cross-sectional characteristics.…”
Section: Control Variablesmentioning
confidence: 99%